2018
DOI: 10.1101/358432
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The functional genomic circuitry of human glioblastoma stem cells

Abstract: SummarySuccessful glioblastoma (GBM) therapies have remained elusive due to limitations in understanding mechanisms of growth and survival of the tumorigenic population. Using CRISPR-Cas9 approaches in patient-derived GBM stem cells to interrogate function of the coding genome, we identify diverse actionable pathways responsible for growth that reveal the gene-essential circuitry of GBM stemness. In particular, we describe the Sox developmental transcription factor family; H3K79 methylation by DOT1L; and ufmyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 78 publications
1
17
0
Order By: Relevance
“…The addition of DOX reduced sphere-forming frequency from 20.4% to 5.3% in GSC523_DDX56 after 2 weeks (Figure 3C). The same experiment in GSC564_DDX56 cells did not alter sphere forming, as expected from the screen data in which DDX56 did not score as an essential gene (Figure 3D) (MacLeod et al, 2019). In total, we confirmed that DDX56 was required for population growth and self-renewal in GSC523 but not GSC564 cells.…”
Section: Cell Reportssupporting
confidence: 85%
See 3 more Smart Citations
“…The addition of DOX reduced sphere-forming frequency from 20.4% to 5.3% in GSC523_DDX56 after 2 weeks (Figure 3C). The same experiment in GSC564_DDX56 cells did not alter sphere forming, as expected from the screen data in which DDX56 did not score as an essential gene (Figure 3D) (MacLeod et al, 2019). In total, we confirmed that DDX56 was required for population growth and self-renewal in GSC523 but not GSC564 cells.…”
Section: Cell Reportssupporting
confidence: 85%
“…In total, 82.5% of all DDX56 + cells co-expressed the NSC marker SOX2, while 43.8% of all SOX2 + cells co-expressed DDX56; 9,564 cells (35.8%) were SOX2 + /DDX56 + , thus supporting frequent DDX56 expression in these stem-like cell populations (Figures S3A-S3C). Several of those GSC lines have been subjected to genome-wide CRISPR screens for gene essentiality (MacLeod et al, 2019). From the screen data, we chose to investigate two GSC lines that demonstrated different essentiality with respect to DDX56: GSC523 (essential) and GSC564 (non-essential).…”
Section: Cell Reportsmentioning
confidence: 99%
See 2 more Smart Citations
“…This superphylum has been joined by recently proposed phyla: Bathyarchaeota, Geoarchaeota and Lokiarchaeota [18]. Another superphylum, DPANN, was proposed in 2013 and includes Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota and Nanohaloarchaeota phyla (Figure 1) [19]. Finally, the phyla Woesearchaeota and Pacearchaeota, described in 2016, were grouped in the DPANN superphylum (Figure 1).…”
Section: Taxonomy Of the Archaeal Domainmentioning
confidence: 89%